Pengaruh Pupuk Kalium Dan Fosfat Terhadap Ketersediaan Dan Serapan Fosfat Tanaman Kacang Tanah (Arachis Hypogaea L.) Pada Tanah Brunizem - Elizabet Kaya (Faculty of Agriculture, Pattimura University, 2012)
The aim of this research was to investigate the availability and uptake of phosphate with the application of potassium and phosphate fertilizers in brunizem soil. The experiment was arranged in a factorial completely Randomized Design which tested various levels of KCl (no calium, 0.2 g/5 kg soil and 0.4 g/5 kg soil) and SP-36 (no fosfat, 0.35 g/5 kg soil and 0.70 g/5 kg soil) fertilizers. The result showed a significant effect of potassium fertilizer treatments on soil pH. The best rate of potassium fertilizer was 0.4 g KCl per pot or 160 kg KCl ha-1. Phosphate fertilizer treatment gave a significant effect on soil pH, available phosphate and phosphate uptake. The best rate of phosphate fertilization was 0.70 g SP-36 per pot or 240 kg SP-36 ha-1.